1989
DOI: 10.1145/75335.75336
|View full text |Cite
|
Sign up to set email alerts
|

In search of knowledge-based search tactics

Abstract: Knowledge-based search tactics are discussed in terms of their role in the functioning of a semantically-based search system for bibliographic information retrieval. This prototype system, EP-X, actively assists users in defining or refining their topics of interest. It does so by applying search tactics to a knowledge-base describing topics in a particular domain and a database describing the contents of individual documents. This paper reviews the empirical studies that lead to the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although early work in IR (Croft and Lewis, 1987;Smith et al, 1989) along these lines have not been successful, recent attempts in question answering (Harabagiu et al, 2000;Small et al, 2004;Demner-Fushman and Lin, 2007) have demonstrated the effectiveness of frame-based retrieval. Recent work on structured queries (Bilotti et al, 2007) lends additional support to the effectiveness of automatic facet analysis, since there is often a correspondence between query clauses and facets.…”
Section: Mediated Search As a Retrieval Modelmentioning
confidence: 99%
“…Although early work in IR (Croft and Lewis, 1987;Smith et al, 1989) along these lines have not been successful, recent attempts in question answering (Harabagiu et al, 2000;Small et al, 2004;Demner-Fushman and Lin, 2007) have demonstrated the effectiveness of frame-based retrieval. Recent work on structured queries (Bilotti et al, 2007) lends additional support to the effectiveness of automatic facet analysis, since there is often a correspondence between query clauses and facets.…”
Section: Mediated Search As a Retrieval Modelmentioning
confidence: 99%
“…In order to evaluate the contents that are associated with the semantics of the data being retrieved, a database management system requires knowledge for interpreting raw data into the contents implied. Knowledgeassisted retrieval is also studied in the area of textual databases [40], [52]. However, it plays a more important role for multimedia database retrieval because even a single media data has many faces of meaning/contents, one of which should actually be referred to in query evaluation depending on a context of retrieval.…”
Section: Introductionmentioning
confidence: 99%